The participation of immigrants in Second Chance Schools, in the region of Central Macedonia - Dakou, Paraskevi; Prokou, Eleni (Adult Education Critical Issues, 2023)
The purpose of this study was to investigate the participation of immigrants in Second Chance Schools (SCS), examining their incentives to participate, the possible barriers they encountered before enrolling, and those they probably face in terms of attendance and/or in the learning process, as well as their perceptions of the learning environment of SCS. 18 in-depth semi-structured interviews were conducted with trained immigrants of 4 Second Chance Schools in the Region of Central Macedonia. The findings indicate that the participants were motivated to enroll in the SCS by both intrinsic and extrinsic incentives, while multiple barriers, mainly situational and/or dispositional, hindered their enrollment. Similar barriers affected their attendance and learning process, along with those that have arisen due to the forced remote operation of SCS for coronavirus containment. However, they have developed a positive attitude towards the learning environment of SCS, emphasizing their satisfaction and praising the support of trainers.